ABOUT THE PRACTICE OF THE IMPLEMENTATION OF THE LEVERS OF STATE INFLUENCE ON THE FINANCIAL AND CREDIT POLICY - Vlasiuk, V. Ye. (Science and Transport Progress, 2007)
The article outlines the basic problems in realization of governmental measures of support of steady economy development and determines the prospective actions as redards state coordination and levers of influence on the financial & credit system in the market environment. It also consders state policy aproaches to introduction of regulatory and corrective factots of influence upon financial & credit system in some countries of the world.